Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Following the steps given in your guide you'll have
1) (x-1)² expanded into a perfect trinomial..
        -square the first term ⇒ x²
        -multiply 2(x)(-1) ⇒ -2x
        -square the last term 1² ⇒ 1
  so you'll have, x²-2x+1 as the perfect trinomial

2&3) distribute 2 to the trinomial you just solved
   2(x²-2x+1) ⇒ 2x²-4x+2

4) add 3
   2x²-4x+2+3 ⇒2x²-4x+5

 so the resulting equation would be:
 y = 2x²-4x+5
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts